Faktor-Faktor Yang Mempengaruhi Akseptor KB Dalam Memilih Kontrasepsi di Bidan Seni Riska Dewi Kecamatan Wampu Kabupaten Langkat Tahun 2023 - Sri Rahayu; Asnita Sinaga (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Family planning is an action that helps individuals or married couples to achieve certain objectives to avoid unwanted births, regulate the interval between pregnancies, control the timing and births in the husband and wife relationship and determine the number of children in the family. Family planning is an effort to space out or plan the number and spacing of pregnancies by using contraception (Manuaba, 2009). Contraception is an effort to prevent pregnancy. This effort can be temporary, it can also be permanent. Contraceptive use is one of the variables that influences fertility (Wiknjosastro, 2005). The main objective of the national family planning program is to meet public demand for quality family planning and reproductive health services, reduce the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR), as well as overcoming reproductive health problems in order to build quality small families (Arum, 2011) . This research was carried out at the Riska Dewi Art Midwife, Wampu District, Langkat Regency in 2023, which provides quality health services. Based on the results of the analysis, it was found that for the educational variable, mothers with elementary school education have no influence on users of non-hormonal contraceptives at a 95% confidence level and can only contribute 1%, mothers with junior high school education also have no influence on users of non-hormonal contraceptives. at a 95% confidence level and can only contribute 41%, while mothers with high school education have no influence on non-hormonal contraceptive users at a 95% confidence level and can only contribute 81%.